Experimental evaluation, FEM and condensed stiffness matrices of 2D external welded haunched joints. (15th February 2020) - Loureiro, Alfonso; Lopez, Manuel; Gutierrez, Ruth; Reinosa, Jose M.
Highlights: Four haunched joints have been tested and calibrated FE models have been developed. Inclined stiffeners increase considerably the stiffness and the resistance. Condensed matrices lead to very good results when compared with FE models. Condensed matrices include the interactions between the joint degrees of freedom. Abstract: In recent years, several researchers have been working hard to improve the knowledge with respect to steel joints behaviour. Special effort has been made for obtaining the stiffness of the different components of the joints, with the aim of introducing this stiffness in the component method in accordance with the EC3. Nevertheless, the component method has important limitations and therefore it is necessary to develop new methods for obtaining the stiffness of joints. In the present work, an alternative method of evaluating the stiffness of 2D external welded haunched joints is presented. The authors show the results of 4 tests and their corresponding finite element models. Four different typologies of joints have been tested, in regards to the stiffening of the column web. The four configurations of joints are the following: Joint 1: with three horizontal stiffeners in the column web. Joint 2: with two horizontal stiffeners and an inclined stiffener in the column web. Joint 3: with two horizontal stiffeners in the column web. Joint 4: without web stiffeners. In all cases, the specimens have been subjected to a point load at the end of the beam, and rotations and displacements have been measured. Additionally, finite element models of the joints have been developed, and they have been properly calibrated with the results obtained in the tests. The condensed stiffness matrices of the joints have been extracted, and they have been tested by means of introducing such matrices into the global analysis of 4 frames, and comparing the obtained results with those ones extracted from the corresponding finite element models. The use of the condensed matrix of the joints presents very good results, and takes into account all the interactions between the different degrees of freedom of the joint.